2008
DOI: 10.1002/we.288
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Weather Research and Forecasting model on forecasting low‐level jets: implications for wind energy

Abstract: Nocturnal low‐level jet (LLJ) events are commonly observed over the Great Plains region of the USA, thus making this region more favorable for wind energy production. At the same time, the presence of LLJs can significantly modify vertical shear and nocturnal turbulence in the vicinities of wind turbine hub height, and therefore has detrimental effects on turbine rotors. Accurate numerical modeling and forecasting of LLJs are thus needed for precise assessment of wind resources, reliable prediction of power ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
142
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(165 citation statements)
references
References 38 publications
8
142
0
7
Order By: Relevance
“…The attempts to model atmospheric events, including LLJs, are not new. Storm et al (2009) conducted research to assess whether numerical weather prediction (NWP) models can replace expensive equipment such as meteorological towers in forecasting LLJs. They found that the Weather Research and Forecasting (WRF) model was able to capture some of the main characteristics of the observed LLJ events; however, WRF proved to be inaccurate in predicting important LLJ features such as peak height and speed.…”
Section: Previous Experiences On Data Collectionmentioning
confidence: 99%
“…The attempts to model atmospheric events, including LLJs, are not new. Storm et al (2009) conducted research to assess whether numerical weather prediction (NWP) models can replace expensive equipment such as meteorological towers in forecasting LLJs. They found that the Weather Research and Forecasting (WRF) model was able to capture some of the main characteristics of the observed LLJ events; however, WRF proved to be inaccurate in predicting important LLJ features such as peak height and speed.…”
Section: Previous Experiences On Data Collectionmentioning
confidence: 99%
“…In a very recent paper, Storm et al (2009) [51] studied the performance of the WRF model in the forecast of low-level jets (LLJs) in the U.S. plains, a common nighttime feature of the atmospheric flow that may lead to increased mean winds in the low troposphere, somewhere between 100 and 1,000 m and occasionally within reach of wind turbines. This study also found mixing results on NWP performance, with hints of a good representation of the essential features of the jets, indicating that the important driving processes are indeed considered by the model.…”
Section: Zhong and Fastmentioning
confidence: 99%
“…Thus, the scientific objective of this study is to estimate and compare the potential impacts of future large scale LUCC on surface temperature from a global perspective. The Weather Research and Forecasting (WRF) model, as the latest-generation numerical weather prediction model [36][37][38], is used as an important tool to quantitatively analyze and compare the possible impacts of the future land use changes of different regions on the regional climate. Section 2 introduces the study areas, especially the characteristics of the dominant land use/cover and the tendency of LUCC.…”
Section: Introductionmentioning
confidence: 99%